Climate structuring of Batrachochytrium dendrobatidis infection in the threatened amphibians of the northern Western Ghats, India. Issue 6 (13th June 2018) - Thorpe, Christopher J.; Lewis, Todd R.; Fisher, Matthew C.; Wierzbicki, Claudia J.; Kulkarni, Siddharth; Pryce, David; Davies, Lewis; Watve, Aparna; Knight, Mairi E.
Abstract : Batrachochytrium dendrobatidis ( Bd ) is a pathogen killing amphibians worldwide. Its impact across much of Asia is poorly characterized. This study systematically surveyed amphibians for Bd across rocky plateaus in the northern section of the Western Ghats biodiversity hotspot, India, including the first surveys of the plateaus in the coastal region. These ecosystems offer an epidemiological model system since they are characterized by differing levels of connectivity, edaphic and climatic conditions, and anthropogenic stressors. One hundred and eighteen individuals of 21 species of Anura and Apoda on 13 plateaus ranging from 67 to 1179 m above sea level and 15.89 to 17.92° North latitude were sampled. Using qPCR protocols, 79% of species and 27% of individuals tested were positive for Bd . This is the first record of Bd in caecilians in India, the Critically Endangered Xanthophryne tigerina and Endangered Fejervarya cf. sahyadris . Mean site prevalence was 28.15%. Prevalence below the escarpment was 31.2% and 25.4% above. The intensity of infection (GE) showed the reverse pattern. Infection may be related to elevational temperature changes, thermal exclusion, inter-site connectivity and anthropogenic disturbance. Coastal plateaus may be thermal refuges from Bd . Infected amphibians represented a wide range of ecological traits posing interesting questions about transmission routes.